From cachexia to obesity: the role of host metabolism in cancer immunotherapy. Issue 4 (December 2019) - Brocco, Davide; Di Marino, Pietro; Grassandonia, Antonino
Abstract : Purpose of review: Currently, several clinical trials in cancer therapy have demonstrated the success of immunomodulatory therapies. However, only a variable fraction of patients actually benefit from these treatments. The understanding of key mechanisms behind this response heterogeneity is one of the major unmet need and intense research field in immuno-oncology. This review will discuss the host metabolic dysfunctions derived from cachexia or obesity that can affect the response to cancer immunotherapy. Recent findings: Preclinical studies demonstrated that chronic inflammation, nutritional intake impairment and endocrine dysfunction may affect anticancer innate and adaptive immunity, both in cachexia and obesity. New emerging clinical findings have highlighted the impact of metabolic biomarkers in predicting response to immune checkpoint inhibitors in cancer patients. Summary: Patient's weight and inflammatory status could be relevant in the clinical decision-making process before starting cancer immunotherapy and for an effective patient selection and stratification in future clinical trials employing this class of anticancer agents.